2013
DOI: 10.1128/jvi.02464-13
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Induces Global Changes in Cellular mRNA Isoform Usage That Are Important for the Maintenance of Latency

Abstract: Oncogenic viruses promote cell proliferation through the dramatic reorganization of host transcriptomes. In addition to regulating mRNA abundance, changes in mRNA isoform usage can have a profound impact on the protein output of the transcriptome. Using Epstein-Barr virus (EBV) transformation of primary B cells, we have studied the ability of an oncogenic virus to alter the mRNA isoform profile of its host. Using the algorithm called SplicerEX with two complementary Affymetrix microarray platforms, we uncovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
3
8
0
Order By: Relevance
“…3′UTR shortening is known to occur in highly proliferative states such as cancer 37,38 . Furthermore, B cells infected with Epstein-Barr virus (EBV) demonstrate reduced 3′UTR lengths for a number of host transcripts 39 . However, EBV establishes a latent infection and immortalizes B cells, and the altered host polyadenylation patterns appear to be a consequence of the associated proliferation rather than the infection itself 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3′UTR shortening is known to occur in highly proliferative states such as cancer 37,38 . Furthermore, B cells infected with Epstein-Barr virus (EBV) demonstrate reduced 3′UTR lengths for a number of host transcripts 39 . However, EBV establishes a latent infection and immortalizes B cells, and the altered host polyadenylation patterns appear to be a consequence of the associated proliferation rather than the infection itself 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, B cells infected with Epstein-Barr virus (EBV) demonstrate reduced 3′UTR lengths for a number of host transcripts 39 . However, EBV establishes a latent infection and immortalizes B cells, and the altered host polyadenylation patterns appear to be a consequence of the associated proliferation rather than the infection itself 39 . However, during lytic HCMV infection, the cells are not proliferative, indicating that global 3′UTR shortening is not a secondary effect of proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate post-transcriptional and and/or post-translational regulation of some genes, like EIF2B4 and UBE2C ( Table 1 and Fig 4C ). To our knowledge, EBER-mediated activation of AKT has not been documented previously even though the PI3K-AKT signaling cascade is a known target of the EBV oncoprotein LMP1 [ 18 , 35 ] and a recent bioinformatics study showed that EBV infection affects alternative splicing [ 53 ]. This apparent redundancy in cell signaling activation mediated by EBER expression and the EBV-encoded oncoprotein LMP1 may explain the lack of effects on EBV transformation potential and latency maintenance observed in the EBER-deletion studies reported previously [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation plays an important role in the switch between the lytic and lysogeny phases by regulating BZLF promoter known as Z. It has been suggested that the balance between recruitment of histone acetyltransferases versus histone deacetylases by transacting factors promotes and decides the switch between latency and lytic reactivation [29]. Viral latency may eventuate in carcinogenesis provided the presence of conducive host (susceptibility factors) and viral (oncogenic latency proteins) exists.…”
Section: Ebv Infection Molecular Interaction and Latencymentioning
confidence: 99%